Nilai Ahap Dalam Sejarah Gereja Kristen Protestan Simalungun (GKPS) Tarutung Tahun 1980 Sampai Dengan 1991 - Meriah Carennika Purba; Erman S Saragih; Megawati Manullang; Herdiana Boru Hombing; Nurelni Limbong (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
Simalungun is one of the ethnic groups that maintains aspects of its culture. Ahap, which has become an identity for the Simalungun people, initially had positive aims and had a positive impact. According to the Simalungun people, Ahap has enormous power to determine human behavior. GKPS Tarutung is proof of the large number of Simaungun people who live in an area where the majority of the population is the Toba Batak tribe. Ahap became an important factor in the history of the founding of the Simalungun Protestant Christian Church (GKPS) Tarutung. The research aims to find out the meaning of Ahap for the Simalungun people of the Tarutung diaspora and to what extent the value of Ahap is in the history of the founding of GKPS in Tarung. The approach used by the author in completing this paper is to use a descriptive approach, namely writing that describes the actual situation of the object under study. According to the actual situation during direct research, the data collected is not in the form of numbers but the data comes from manuscripts, interviews, field notes, personal documents, memos and other documents. According to St. Mardinus Sinaga, SH, Ahap as the initial trigger for the formation of the PKSTS Organization. This is evident from the fact that the PKSTS organization was started by a meeting between two young men from the Simarmata clan and the Purba clan, who talked about relatives and family from the Simalungun tribe.